(untitled) (Journal of Science and Technology, 2016)
From the general relationship between specific energy and flow depth for all open channels, the specific relationship for parabolic open channels was obtained here. By introducing suitable scaling parameters of the same length dimensions as the specific energy and flow depth, a rela-tionship was obtained between a dimensionless specific energy and a dimensionless flow depth, which is applicable to any parabolic open channel at any discharge. This is presented in both tabular and graphical forms which allows the flow depth to be obtained without iteration, for any given specific energy and discharge in any parabolic open channel.